Testing of nylon 6 nanofibers with different surface densities as sorbents for solid phase extraction and their selectivity comparison with commercial sorbent - Háková, Martina; Raabová, Hedvika; Havlíková, Lucie Chocholoušová; Chocholouš, Petr; Chvojka, Jiří; Šatínský, Dalibor (Talanta, 2018)
Nylon 6 nanofibers were tested for their ability to serve as a sorbent for solid phase extraction (SPE). The regular nanostructure providing a great sorption area and amidic functionality should lead to the assumption that nylon 6 nanofibers could be used as a novel sorbent with great potential for sample pre-treatment. However, due to the substantial differences between classical particle sorbents used for solid phase extraction and nanofibers, it is necessary to evaluate this novel approach. This article describes three types of laboratory fabricated nylon 6 nanofibers with different surface density (5.04gm-2, 3.90gm-2 and 0.75gm-2) and corresponding surface areas for solid phase extraction of several groups of compounds with different structural and physicochemical properties (parabens, steroids, flavonoids and pesticides). The nanofibers were created by needleless electrospinning. Extraction columns were manually packed in classic 1- or 3-mL plastic syringe cartridges with 26-30mg of nanofibers and the column bed was sealed with polypropylene frits. The SPE procedure followed a typical five-step protocol and the collected eluates were analyzed by HPLC with UV detection. Extraction recovery was used as a parameter to evaluate the behavior of the analytes within the SPE process. Under this set condition, the recovery of the SPE process ranged from 23.1% to 125.8%. SPE showed good repeatability (0.58-11.87% RSD) and inter-day reproducibility (3.86-9.79% RSD). The achieved results were compared with SPE using a classic particle sorbent column. Good mechanical and chemical stability of nanofibers was proved. Scanning electron microscope was used for the evaluation of morphological changes in nanostructure. Nylon 6 nanofibers proved being a cost-effective sorbent for repeated use in SPE. Nylon 6 nanofibers have great potential in miniaturized SPE enabling users to overcome troubles with high back-pressure.
Keywords: Nanofibrous extraction; SPE; Nanofiber polymers